THE USE OF CARTOONS IN POPULAR PROTESTS THAT FOCUS ON GEOGRAPHIC, SOCIAL, ECONOMIC AND POLITICAL ISSUES - TOTRY, Mary; MEDZINI, Arnon (European Journal of Geography, 2013)
The comics and related arts (cartoons, graffiti, illustrated posters and signs) have always played an important role in shaping public protests. From the French Revolution to the recent Arab Spring revolutionary wave of demonstrations and protests, these visual means have stood out thanks to their ability to transmit their message quickly, clearly and descriptively. Often these means have enabled the masses to see their social, economic and political reality in a new and critical light. Social, economic and political cartoons are a popular tool of expression in the media. Cartoons appear every day in the newspapers, often adjacent to the editorials. In many cases cartoons are more successful in demonstrating ideas and information than are complex verbal explanations that require a significant investment of time by the writer and the reader as well. Cartoons attract attention and curiosity, can be read and understood quickly and are able to communicate subversive messages camouflaged as jokes that bring a smile to the reader’s face. Cartoons become more effective and successful in countries with strict censorship and widespread illiteracy, among them many countries in the Arab world. Cartoonists are in fact journalists who respond to current events and express their opinions clearly and sometimes even scathingly and satirically. They translate political, social and economic issues into locally familiar cultural symbols, as well as using symbols that are universally recognized. The products of their work complement social protests arising from the street. The objective of this paper is to demonstrate how cartoons can be used to understand geographic, social, economic and political processes by focusing on the cartoons of Naji Al-Ali as a case study.